Performance analysis and evaluation of IEEE 802.11 distributed coordination function using OPNET - Zaynab Mahir Abdel-Ameer; Abdul Kareem A. Najem Alaloosy; Khattab M. Ali Alheeti (Bulletin of Electrical Engineering and Informatics, 2020)
This paper discusses the distributed coordination function (DCF) access mechanism which is a carrier sense multiple access with collision avoidance (CSMA/CA) scheme. Simulation projects for different DCF performance parameters have been built using the OPNET network simulator. The projects are mainly basic service set (BSS) topology simulated under different parameter values (data rate, fragmentation, RTS/CTS, number of nodes, and load condition). Simulation results show when the DCF access mechanism is better under what load condition, and how to choose the best fragmentation threshold and other access-mechanism specific parameters according to the network conditions. Simulation results were validated against a theoretically calculated maximum throughput (the simulation maximum throughput was about 70% of the theoretically calculated maximum throughput).